Legume cover under Camellia oleifera forests enhances understory biomass carbon storage and soil CO2 flux but declines soil inorganic carbon storage on a karst steep slope - Ding, Leilei; Sun, Hang; Long, Zhongfu; Gao, Birong; Zhou, Zhenduan; Ye, Yue; Yang, Song; Lei, Xia (Frontiers in Microbiology, 2026)
IntroductionLegume cover is a widely used and useful soil management strategy in orchards across the world. However, it remains unclear how the alfalfa cover affects vegetation and soil carbon storage, soil greenhouse gas fluxes, and global warming potential in Camellia oleifera forests. Furthermore, the understory vegetation, soil physicochemical properties, and microorganisms as potential drivers of vegetation and soil carbon storage, soil greenhouse gas fluxes, and global warming potential remain unexplored.MethodsThis study determined vegetation and soil carbon storage, soil greenhouse gas fluxes, and global warming potential under legume cover and non-cropping cover and explored the potential drivers on a karst steep slope.ResultsThe results showed that cropping cover under Camellia oleifera forests elevated understory vegetation aboveground and vegetation root biomass carbon storage (p = 0.0002) and reduced soil N2O flux (p = 0.0210), but reduced soil inorganic carbon storage (p = 0.0003) and enhanced soil CO2 flux (p = 0.0002) and global warming potential (p = 0.0002). In addition, cropping cover not only increased understory vegetation species richness (p = 0.0104), aboveground biomass (p = 0.0002), and vegetation root biomass (p = 0.0009) but also decreased soil microbial carbon (p = 0.0360) and phosphorus limitation (p = 0.0104) and enhanced soil organic carbon decomposition (p = 0.0043). Moreover, cropping cover shifted microbial community assembly processes and life-history strategies and enhanced soil bacterial community stability (p = 0.0000) and soil bacterial and fungal network stability. A trade-off existed between understory vegetation aboveground (Spearman r = −0.69, p = 0.0030) and vegetation root biomass carbon storage (Spearman r = −0.62, p = 0.0099) and soil inorganic carbon storage.DiscussionAlfalfa cover is recommended for improved understory vegetation aboveground and vegetation root biomass carbon storage, soil physicochemical properties, and soil microbial community stability and network stability, whereas it may not be recommended due to increased soil CO₂ flux and global warming potential, as well as reduced soil inorganic carbon storage. This study first demonstrated the trade-off between understory vegetation aboveground and vegetation root biomass carbon storage and soil inorganic carbon storage, and this trade-off should be carefully considered when conducting multi-storage management.